Governance in Albania : A Way Forward for Competitiveness, Growth, and European Integration - World Bank (Washington, DC, 2013)
Since its emergence from a turbulent post-communist transition, Albania has achieved remarkable progress in economic and social development. Governance improvements, especially in the effectiveness of public administration, have been instrumental to the country's impressive economic performance and improved human development outcomes. The Government has taken steps to improve public order and personal safety, particularly through efforts to crack down on violent and organized crime. Despite these positive developments, Albania continues to face significant governance challenges that will need to be overcome if the country is to achieve critical development objectives. Enduring politicization of the public administration and incomplete separation of powers, exemplified by instances of political interference in judicial processes, remain serious obstacles. The Government recognizes the need to accelerate progress on several dimensions of governance reform, particularly in light of its aspirations to European Union (EU) accession. This issue brief seeks to analyze the nature and recent evolution of Albania's governance environment, to identify the principal governance constraints to the achievement of development priorities-overall and in key sectors, and to outline recommendations for the way forward.